Extremism in the Discourse of Sayyid Quṭb: Myth and Reality - Ushama, Thameem (Intellectual Discourse, 2008)
Abstract: Sayyid Quṭb has been much maligned in the West as well as in the Muslim World as an extremist and a radical whose writings have been the inspirational source of international terrorism. A discourse analysis of his writings shows that his views about Western culture and civilisation, the Zionist conspiracy to undermine the ummah, and Western education were highly critical and harsh, and these may have given the impression that he is a radical. His explanation of such concepts as tawḥīd, Islamic society and the infidelity of Muslim rulers may have added further impetus to the charge of extremism. These concepts, however, were explained by Quṭb with reference to the Qur´ān and the Sunnah and has precedence in the writings of other Muslim scholars. Further, Quṭb however advocated a peaceful, incremental methodology for the Islamic movement and personally abhorred armed tactics as means to usher in an Islamic society and state.